The Socio-Economic Impacts of Agrarian Exploitation through Irrigation Systems during the Dutch East Indies Period - Yandi Syahputra Hasibuan; Kiki Maulana Affandi; Junaidi Nasution (Warisan: Journal of History and Cultural Heritage, 2025)
This article examines the socio-economic impacts of agrarian exploitation during the Dutch East Indies period by positioning irrigation systems as a central instrument of colonial agricultural policy. From the implementation of the forced cultivation system (cultuurstelsel) to the era of economic liberalization, the expansion of irrigation networks functioned not merely as technical infrastructure but as a mechanism of control over land, labor, and agrarian production among indigenous communities. This study employs historical research methods, including source collection (heuristics), source criticism, interpretation, and historiography, drawing upon colonial archival materials, technical reports of the Dutch East Indies government, and relevant historiographical studies. The findings reveal that while colonial irrigation development increased agricultural productivity and generated economic surplus for the colonial state, it simultaneously intensified labor exploitation, reinforced social inequality, and marginalized indigenous irrigation systems. The legacy of colonial irrigation infrastructure continues to shape contemporary water management practices and agrarian relations in Indonesia.